Rear - end heavy vehicle crash analysis using ANSYS - Jagatheesvaran, Uvaaraj (2022)
Accidents involving heavy vehicles are frequently reported in newspapers and other forms of public media. As a result, the visibility of heavy vehicle is capable of preventing unexpected incidents, such as rear-end collisions. Some issues on visibility of heavy vehicles will be briefly discussed where some of the existing safety features in terms of visibility will be reviewed and improvements will be suggested. Besides, the performance of heavy vehicles to carry loads when climbing the hill will also be analyzed. The methods for this project consist of survey, calculations, and computer simulations. The preliminary survey is to investigate the general awareness on visibility of heavy vehicles that encompasses the warning signal like the lights, light reflection stickers, and the color of canvas used at the back of heavy vehicles. Although the lights on heavy vehicles might be insufficient, light reflection stickers can be an aid to light the heavy vehicles. As for the canvas used, it is recommended to use only bright color canvas covers for heavy vehicle. The speed required for the heavy vehicles to climb a hill with certain load have been identified to be important as well, where the required speed can be a guide for drivers where they need to maintain the minimum speed to pass the hill smoothly. Other road users also will move up the hill smoothly without disturbance by heavy vehicles obstructing a lane at the hills and the usual congestion caused by heavy vehicles also can be reduced. In addition, the simulations on the impact analysis also have been made by using ANSYS where the collisions between car and heavy vehicle can be studied. This is also to simulate the use of safe speed between cars and heavy vehicles. Hence, the conclusion can be made as the slower the speed the higher the stress faced by the car and its condition will become worse.